Winter melt conditions of the inland ice cap on King George Island, Antarctic Peninsula - Falk, Ulrike; Sala, Hermán (ERDKUNDE, 2015)
The South Shetland Islands are located at the northern tip of the Antarctic Peninsula (AP) which is among the fastest warming regions on Earth. Surface air temperature increases ( 3 K in 50 years) are concurrent with retreating glacier fronts, an increase in melt areas, ice surface lowering and rapid break-up and disintegration of ice shelves. We have compiled a unique meteorological dataset for the King George Island (KGI)/Isla 25 de Mayo, the largest of the South Shetland Islands. It comprises high-temporal resolution and spatially distributed observations of surface air temperature, wind directions and wind velocities, glacier ice temperatures in profile with a fully equipped automatic weather station as well as snow accumulation and ablation measurements on the Warszawa Icefield, since November 2010 and ongoing. In combination with long-term synoptic datasets (40 and 10 years, respectively) and atmospheric circulation indices datasets, we have looked at changes in the climatological drivers of the glacial melt processes, and the sensitivity of the inland ice cap with regard to winter melting periods and pressure anomalies. The analysis has revealed a positive trend of 5 K over four decades in minimum surface air temperatures for winter months, clearly exceeding the published annual mean statistics, associated to a negative trend in mean monthly winter sea level pressure. This concurs with a positive trend in the Southern Annular Mode (SAM) index, which gives a measure for the strength and extension of the Antarctic vortex. We connect this trend with a higher frequency of low-pressure systems hitting the South Shetland Islands during austral winter, bringing warm and moist air masses from lower latitudes. A revision of spatial and seasonal changes in adiabatic air temperature lapse rates reveals the high sensitivity of the upper ice cap to free atmospheric flow and synoptic changes. Observed surface air temperature lapse rates show a high variability during winter months (standard deviations up to ±1.0 K/100 m), and a distinct spatial variability reflecting the impact of synoptic weather patterns especially during winter glacial mass accumulation periods. The increased mesocyclonic activity during the winter time in the study area results in intensified advection of warm, moist air with high temperatures and rain, and leads to melt conditions on the ice cap, fixating surface air temperatures to the melting point. This paper assesses the impact of long-term change in large-scale atmospheric circulation and variability and climatic changes on the atmospheric surface layer and glacier mass accumulation of the upper ice cap during winter season for the Warszawa Icefield on KGI. Supplementary data are available at http://dx.doi.org/10.1594/PANGAEA.848704